Pengaruh Efikasi Diri dan Pengembangan Karir terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Mediasi (Studi Kasus pada Setjen Kemenag RI) - Fransiskus Haris Leonard; Widjaja, Bernard T.; Purnama, Eka Desy (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This study aims to analyze the effect of self-efficacy on employee performance, analyze the effect of career development on employee performance, analyze the effect of work motivation on employee performance, analyze the effect of self-efficacy on work motivation, analyze the effect of career development on work motivation, analyze the effect of self-efficacy on employee performance through work motivation, analyze the effect of career development on employee performance through work motivation. The method in the study was based on interviews and questionnaires. The sample processed was 227 employees obtained from the Slovin formula. The study was conducted using a descriptive analysis method using a questionnaire. The method of calculating this data will be processed using the Smart PLS application. The results of this study are that Self-Efficacy has a positive and significant effect on employee performance (employees at the Secretariat General of the Ministry of Religious Affairs of the Republic of Indonesia). Career development has a positive and significant effect on employee performance (employees at the Secretariat General of the Ministry of Religious Affairs of the Republic of Indonesia). Work motivation has a positive and significant effect on employee performance (employees at the Secretariat General of the Ministry of Religious Affairs of the Republic of Indonesia). Self-Efficacy has a positive and significant effect on work motivation.